Extraction of temperature-dependent exciton-polariton damping in InP bulk crystal - S. A. Vaganov (JOURNAL OF ADVANCES IN PHYSICS, 2020)
The temperature dependence of exciton-polariton damping in InP bulk crystal was extracted by the method of integrated absorption. The extraction procedure excluding the contribution of inhomogeneous broadening into the exciton ground state absorption linewidth is graphically illustrated. The extracted temperature-dependent damping is analyzed regarding the primary dissipative mechanism in order to determine the material parameters of exciton-polariton scattering by acoustic and optical phonons.